BO‘LAJAK MUSIQA O‘QITUVChILARINING KASBIY TAYYORGARLIGIDA DOSTON IJROChILIGI AN’ANALARIDAN FOYDALANISh KOMPONENTLARI - Annakulova, D.B. (SCIENCE and SOCIETY, 2025)
This article analyzes the components of using the traditions of doston performance in improving the professional training of future music teachers. Using the traditions of Uzbek folk doston (epic) performance is one of the most important tools in improving the professional training of future music teachers. The content of education is one of the main categories of music pedagogy, as well as the development of the student's personality.
Keywords: epic; bakhshi; component; cognitive; creative; motivational; local style; music; jirov performance